The Effectiveness of Total Physical Response in the Teaching Speaking Skill - Moh. Mahmud (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
The method of teaching-learning always done by the teacher, where the students still study in the class with the teacher. But, it will not be running well, when the strategy as a method of teaching cannot be understood by a student and cannot support them to evolve and motivate their study. Basically, Total Physical response consists of management or action that is given by instructor or teacher that is related to physical respond clearly.In this research, the data resources are gotten from the pre-test score, post-test score, interview, and documentation. The research used experimental approach. The students as the object were divided to be two classes, they consist of experimental class and control class. The researcher gives a comparison between an experimental class that is given treatment by Total Physical Response and control class by translation. The research design was correlation relational study. This research calculates the data of pre-test and post-test with a formula of product moment. The result of computing correlation coefficient (ro) of TPR 1,000 and rtable indicate 0,800-1,000 is high. So that, there is an influence of Total Physical Response for improving student's speaking skill because it gets "high" value in rtable of the influence of TPR. From the result above, the influence is 100 % from TPR.